Monitoring scan asymmetry of microwave humidity sounding channels using simultaneous all angle collocations (SAACs). Issue 3 (14th February 2013) - John, Viju O.; Holl, Gerrit; Atkinson, Nigel; Buehler, Stefan A.
Abstract: [1] Simultaneous all angle collocations (SAACs) of microwave humidity sounders (AMSU‐B and MHS) on‐board polar orbiting satellites are used to estimate scan‐dependent biases. This method has distinct advantages over previous methods, such as that the estimated scan‐dependent biases are not influenced by diurnal differences between the edges of the scan and the biases can be estimated for both sides of the scan. We find the results are robust in the sense that biases estimated for one satellite pair can be reproduced by double differencing biases of these satellites with a third satellite. Channel 1 of these instruments shows the least bias for all satellites. Channel 2 has biases greater than 5 K, thus needs to be corrected. Channel 3 has biases of about 2 K and more and they are time varying for some of the satellites. Channel 4 has the largest bias which is about 15 K when the data are averaged for 5 years, but biases of individual months can be as large as 30 K. Channel 5 also has large and time varying biases for two of the AMSU‐Bs. NOAA‐15 (N15) channels are found to be affected the most, mainly due to radio frequency interference (RFI) from onboard data transmitters. Channel 4 of N15 shows the largest and time varying biases, so data of this channel should only be used with caution for climate applications. The two MHS instruments show the best agreement for all channels. Our estimates may be used to correct for scan‐dependent biases of these instruments, or at least used as a guideline for excluding channels with large scan asymmetries from scientific analyses. Key Points: Robust scan‐dependent bias patterns are estimated using SAACs Significant scan‐asymmetry is found for some of the channels Main reason for these biases is RFI